Конструювання і розрахунок мостового однобалкового крана ливарного цеху вантажопідйомністю 12 т - Макаріцький, Вячеслав Олександрович; Makaritskyi, Viacheslav (ЦНТУ, 2025)
Кваліфікаційна робота на першому (бакалаврському) рівні вищої освіти на тему: “Конструювання та розрахунок мостового однобалкового крана ливарного цеху вантажопідйомністю 12 т” складається з п’яти розділів. В роботі за вихідними даними виконано конструювання і проектний розрахунок мостового однобалкового крана ливарного цеху вантажопідйомністю 12 т. Qualification work at the first (bachelor's) level of higher education on the topic: “Design and calculation of a single-girder bridge crane in the foundry with a lifting capacity of 12 tons” consists of five sections. In the work, based on the initial data, the design and design calculation of a single-girder bridge crane for a foundry with a lifting capacity of 12 tons was performed.
Design and calculation of a single-girder bridge crane in the foundry with a lifting capacity of 12 tons
Keywords: мостовий однобалковий кран; візок; барабан; гакова підвіска; single-girder overhead crane; trolley; drum; hook suspension